Defective NK cell activity in a mouse model of eczema herpeticum - Kawakami, Yuko (J Allergy Clin Immunol, 2016)
BACKGROUND: Patients with atopic dermatitis (AD) are susceptible to several viruses including herpes simplex virus (HSV). Some patients develop one or more episodes of a severe skin infection by HSV, termed eczema herpeticum (EH). There are numerous mouse models of AD, but no established model exists for EH. OBJECTIVE: We sought to establish and characterize a mouse model of EH. METHODS: We infected AD-like skin lesions with HSV1 to induce severe skin lesions in a dermatitis-prone mouse strain of NC/Nga. Gene expression was investigated by microarray and quantitative PCR; antibody titers were measured by ELISA; natural killer (NK) cell, cytotoxic T cell, regulatory T cell and follicular helper T cell populations were evaluated by flow cytometry. The role of NK cells in HSV1-induced development of severe skin lesions was examined by depletion and adoptive transfer. RESULTS: Inoculation of HSV1 induced severe erosive skin lesions in eczematous mice, which had impaired skin barrier, but milder lesions in small numbers of normal mice. Eczematous mice exhibited lower NK cell activity, but similar cytotoxic T cell activity and humoral immune responses, compared with normal mice. The role of NK cells in controlling HSV1-induced skin lesions was demonstrated by experiments depleting or transferring NK cells. CONCLUSION: A murine model of EH with impaired skin barrier was established in this study. We demonstrated a critical role of defective NK activities in the development of HSV1-induced severe skin lesions in eczematous mice.